2021
DOI: 10.1002/lary.29957
|View full text |Cite
|
Sign up to set email alerts
|

Otolaryngology Department and Society Leadership: Evaluation of Diversity in a Nationwide Study

Abstract: Objectives/Hypothesis Diversity in medicine positively influences healthcare delivery. As we aim to make otolaryngology more diverse, it is essential to analyze our current leadership. Study Design Observational study. Methods A total of 262 department chairs and chiefs, residency program directors, and assistant and associate directors from 117 otolaryngology residency programs as well as 92 society leaders from nine otolaryngology national societies from 2010 to 2020 in the United States are included in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…found that being a man was significantly associated with having a full professorship title (P < .0001) [ 12 ]. Men and women have significantly different h-indexes (P < .0001) across all residency leadership positions [ 12 ]. Only 30% of residency program directors are women, which further supports that women are increasingly under-represented in leadership roles in otolaryngology [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…found that being a man was significantly associated with having a full professorship title (P < .0001) [ 12 ]. Men and women have significantly different h-indexes (P < .0001) across all residency leadership positions [ 12 ]. Only 30% of residency program directors are women, which further supports that women are increasingly under-represented in leadership roles in otolaryngology [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] We read with interest the article by Uppal and colleagues on otolaryngology departmental and societal leadership. 7 The authors found that otolaryngology has an underrepresentation of women and specific ethnic-racial group leadership, underscoring the importance of recognizing underrepresented women leaders in medicine. These trailblazers elevate the specialty with their achievements and inspire the next generation through role modeling, mentoring, and sponsorship-contributions often underappreciated.…”
mentioning
confidence: 99%
“…5 Addressing the cost burden of away rotations could improve the pathway for URiM applicants in otolaryngology, which has significant race-and sex-based disparities in resident selection and faculty promotion. [6][7][8][9] Although virtual away rotations cannot replace the experience gained from in-person clinical rotations, they can allow applicants to build their knowledge base, showcase their skills, and evaluate their fit with a residency program without incurring the expenses of inperson away rotations. Given the potential role of virtual away rotations in future residency recruitment and selection cycles, further investigation into their effectiveness is warranted.…”
mentioning
confidence: 99%
“…Applicant‐reported data from the 2018 to 2020 match years in otolaryngology suggest an average spending of about $2437 for away rotations per applicant over the course of an application cycle 5 . Addressing the cost burden of away rotations could improve the pathway for URiM applicants in otolaryngology, which has significant race‐ and sex‐based disparities in resident selection and faculty promotion 6‐9 …”
mentioning
confidence: 99%